Exploring the influence of teacher-student relationships on Chinese language learning through the mediating role of student's self-efficacy: Foreign language classroom anxiety as a moderator - Ran An; Huan Zhang; Ahsan Akbar; Syed Arslan Haider (Acta Psychologica)
This study aims to examine the impact of the teacher-student relationship (TSR) on learning Chinese as a second language among Pakistani students. We also explore the mediating role of student's self-efficacy and the moderating influence of foreign language classroom anxiety (FLCA). Data were collected from 422 Pakistani students enrolled in Chinese language courses using purposive and convenience sampling techniques. The study employed quantitative methods, utilizing the partial least squares-structural equation modeling technique with SmartPLS 4 software. The result revealed that the teacher-student relationship positively and significantly influence on Chinese language learning. Likewise, student's self-efficacy positively and significantly mediates the relationship between TSR and Chinese language learning. Hence, teachers shall demonstrate empathy, treat students fairly, offer praise, and encourage them to boost students' self-efficacy. Lastly, the study found that foreign language classroom anxiety plays a significant and positive moderating role between TSR and student self-efficacy suggesting that effective communication and mutual understanding are key components of a strong TSR. However, the moderating influence of foreign language classroom anxiety between TSR and Chinese language learning is not significant. The study findings offer important empirical, and practical contributions.